Effect of different organic amino cations on SAPO‐34 for PES/SAPO‐34 mixed matrix membranes toward CO2/CH4 separation. Issue 18 (18th January 2016) - Ahmad, N. N. R.; Mukhtar, H.; Mohshim, D. F.; Nasir, R.; Man, Z.
ABSTRACT: Mixed matrix membranes (MMMs) embedded with functionalized SAPO‐34 were successfully synthesized and characterized. Two different types of organic amino cation, namely ethylenediamine (EDA) and hexylamine (HA), were used to functionalize SAPO‐34 particles prior to MMM synthesis. In this work, the effects of different functionalizing agents on the membrane morphology, pore size, and CO2 /CH4 gas separation properties were investigated. Surface modification of SAPO‐34 was confirmed via X‐ray photoemission spectroscopy (XPS) where the presence of nitrogen atom was observed for the samples functionalized with amino cations. The dispersion of EDA‐functionalized SAPO‐34 particles was found to have better polymer/filler interface morphology as shown by field emission scanning electron microscopy (FESEM) analysis. The gas separation performance revealed that PES containing EDA‐functionalized SAPO‐34 exhibited better CO2 /CH4 separation performance as compared to the MMMs containing HA‐functionalized SAPO‐34. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43387. Abstract :